2003
DOI: 10.1081/rrs-120025568
|View full text |Cite
|
Sign up to set email alerts
|

Binding Interactions of Antagonists with 5‐Hydroxytryptamine3AReceptor Models

Abstract: Homology modeling was performed on the N-terminal extracellular regions of human, mouse, and guinea pig 5-hydroxytryptamine type 3A receptors (5-HT3R) based on the 24% sequence homology with and on the crystal structure of the snail acetylcholine binding protein (AChBP). Docking of 5-HT3 antagonists granisetron, tropisetron, ondansetron, dolasetron ('setrons), and (+)-tubocurarine suggests an aromatic binding cleft behind a hydrophilic vestibule. Several intra- and interface interactions, H-bonds, and salt bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 33 publications
11
70
0
Order By: Relevance
“…In the current study we have used this model to dock the 5-HT 3 receptor antagonist granisetron. During the course of this work a similar study using a range of antagonists was published (10). This study supported our previous work by indicating that some of the residues that we had identified as critical for 5-HT binding and/or function in the binding pocket are also critical for antagonist binding.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…In the current study we have used this model to dock the 5-HT 3 receptor antagonist granisetron. During the course of this work a similar study using a range of antagonists was published (10). This study supported our previous work by indicating that some of the residues that we had identified as critical for 5-HT binding and/or function in the binding pocket are also critical for antagonist binding.…”
supporting
confidence: 77%
“…4) and also aromatic interactions with Tyr-234 and Trp-183. Additionally, in this model granisetron is in the same orientation as predicted by Maksay et al (10), who show that it best fits the 5-HT 3 receptor antagonist pharmacophore model in this orientation. Consequently, we propose that granisetron is located in the binding pocket with its aromatic rings positioned between Trp-183 and Tyr-234, and its azabicyclic ring is close to Trp-90 and Phe-226.…”
Section: Fig 2 Representative Examples Of the Three Model Typessupporting
confidence: 54%
“…This approach has been made possible by the availability of the high resolution structure of the acetylcholine binding protein (AChBP), which is homologous to the extracellular domain of the nicotinic ACh receptor (6). Using this as a template, computer-generated models of ligandbinding pockets of Cys loop receptors, combined with previous data from structure-activity studies, have identified important features of these pockets and on the orientation of agonists and antagonists when located in their binding sites (7)(8)(9)(10)(11)(12)(13). Generating an accurate representation of the orientation of GABA in the GABA C receptor-binding site could identify the processes involved in ligand recognition at this receptor and would also assist in drug design; current data indicate that drugs acting on GABA C receptors could possibly be used to treat visual, sleep, and cognitive disorders (4,14).…”
Section: Gabamentioning
confidence: 99%
“…Nevertheless, homology models have been produced for many receptors, and a range of ligands docked into their binding sites (e.g. Abdel-Halim et al 2008 ;Cromer et al 2002 ;Le Novere et al 2002 ;Maksay et al 2003 ;Reeves et al 2003 ;Schapira et al 2002 ;Trudell & Bertaccini, 2004 ;Yan & White, 2005). The ability of 5-HT 3 Rs to form homomeric receptors means that they are a relatively simple system for molecular modelling, and they have the considerable advantage that the experimental determination of the effects of amino acid substitutions on the properties of the receptor is straightforward.…”
Section: The Ligand-binding Sitementioning
confidence: 99%
“…The 5-HT 3 R is a typical Cys-loop receptor, and has the advantage that it functions as a homomeric receptor, which simplifies the interpretation of experimental data. This protein has also been used extensively in homology modelling and ligand docking (Maksay et al 2003 ;Reeves et al 2003 ;Thompson et al 2005 ;Yan & White, 2005). As this technique is becoming an accepted route to understanding the structural details of the proteins, we use the new homology models and docked ligands to explore the validity of these techniques to define specific molecular interactions with agonists and antagonists in the 5-HT 3 ligand-binding site.…”
Section: Introductionmentioning
confidence: 99%